2019
DOI: 10.1038/s41612-019-0097-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation and composition of the UTLS aerosol

Abstract: Stratospheric aerosol has long been seen as a pure mixture of sulfuric acid and water. Recent measurements, however, found a considerable carbonaceous fraction extending at least 8 km into the stratosphere. This fraction affects the aerosol optical depth (AOD) and the radiative properties, and hence the radiative forcing and climate impact of the stratospheric aerosol. Here we present an investigation based on a decade (2005-2014) of airborne aerosol sampling at 9-12 km altitude in the tropics and the northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…One important wavelength band is 200 to 242 nm, where photolysis of O 2 is responsible for formation of ozone and photolysis of N 2 O produces odd nitrogen (NO y ) (Brasseur and Solomon, 1986). For purely scattering particles, changes in photolysis in this wavelength range are reduced by large cancellations in direct and diffuse light (Michelangeli et al, 1989). Light scattering by the El Chichón volcanic cloud was estimated to reduce O 2 photolysis by about 10 % (Michelangeli et al, 1989).…”
Section: Ultraviolet Scattering and Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important wavelength band is 200 to 242 nm, where photolysis of O 2 is responsible for formation of ozone and photolysis of N 2 O produces odd nitrogen (NO y ) (Brasseur and Solomon, 1986). For purely scattering particles, changes in photolysis in this wavelength range are reduced by large cancellations in direct and diffuse light (Michelangeli et al, 1989). Light scattering by the El Chichón volcanic cloud was estimated to reduce O 2 photolysis by about 10 % (Michelangeli et al, 1989).…”
Section: Ultraviolet Scattering and Absorptionmentioning
confidence: 99%
“…For purely scattering particles, changes in photolysis in this wavelength range are reduced by large cancellations in direct and diffuse light (Michelangeli et al, 1989). Light scattering by the El Chichón volcanic cloud was estimated to reduce O 2 photolysis by about 10 % (Michelangeli et al, 1989). The overall effect of scattering seems to be to reduce ozone formation (Pitari et al, 2014).…”
Section: Ultraviolet Scattering and Absorptionmentioning
confidence: 99%
“…An in depth analysis of the physicochemical aspects of SOAs formation in the upper troposphere and stratosphere is beyond the scope of this work. The reader is referred to published literature on the subject (Hallquist et al, 2009; Martinsson et al, 2019; Yee et al, 2013).…”
Section: Estimation Of Injected Stratospheric Aerosol Massmentioning
confidence: 99%
“…The particle's organic mass fraction ranged from 30 wt% to 70 wt%, depending on the altitude and the air mass origin (Froyd et al, 2009). A recent study, spanning 10 years of filter measurements, showed a dominant contribution of sulfate or organics depending on location, altitude, and season (Martinsson et al, 2019). In a recent study, Höpfner et al (2019) detected and identified crystalline ammonium nitrate particles in the upper troposphere during the Asian monsoon period.…”
Section: Introductionmentioning
confidence: 98%